Multi-spectral Characteristics of Arc Discharge in Switch Cabinet. Issue 1 (1st October 2022) - Miao, Jin; Chen, Ping; Wu, Junfeng; Fei, Bin; Wu, Xu; Liu, Wei; Wan, Jiefeng; Wang, Yue
Abstract: The partial discharge (PD) in high voltage switch cabinet might develop into non-penetrating or penetrating arc under extreme conditions, which can lead to insulation failure in severe case. From the optical radiation characteristics of discharge, an optical detection method for abnormal arc was proposed. Multi-spectral characteristics of arc discharge were obtained by the synchronous monitoring of ultraviolet, visible, and infrared optical signals, and the average intensity of light pulse, average light intensity ratio and the light intensity ratio of three bands were analyzed. The results show that the average light pulse intensity of arc discharge and the proportion of three-band light intensity have obvious characteristics and there is a good corresponding relation between the amplitude of discharge light signal and the applied voltage.